Promoting the wellbeing of the whole person: a within-subjects mixed-methods study exploring the effects of the flourishing intervention among individuals with depressive symptoms - Braghetta, Camilla Casaletti; Gonçalves, Juliane Piasseschi de Bernardin; Alvarenga, Willyane de Andrade; Cowden, Richard G.; Gorenstein, Clarice; Lucchetti, Giancarlo; Vallada, Homero (Frontiers in Psychiatry, 2025)
ObjectiveThis study examines the effect of the Flourishing Intervention on depressive symptoms and wellbeing among individuals with moderate to moderately severe depressive symptoms. The study also seeks to understand participants’ experiences, acceptability, and satisfaction with the intervention.MethodsA quasi-experimental pre-post mixed-methods design was used, incorporating an embedded approach in which descriptive qualitative data complemented quantitative data. The Flourishing Intervention consisted of a 12-week online group-based program, with each session lasting approximately 90 minutes. The study included 98 participants (18–59 years) with moderate to moderately severe depressive symptoms on the Patient Health Questionnaire-9 (PHQ-9), who had completed elementary school or better, resided in São Paulo, and had internet access. All participants were assessed immediately before and after the intervention using the PHQ-9, the Beck Depression Inventory-II (BDI-II), and a range of secondary outcome measures.ResultsEvidence supported improvements in depressive symptoms postintervention (d=-1.14 for PHQ-9 and d=-1.24 for BDI-II). Positive postintervention changes were also observed for anxiety symptoms, personal flourishing, spirituality, quality of life, religious/spiritual coping, social support, happiness, gratitude, forgiveness, and life satisfaction.ConclusionThe Flourishing Intervention has the potential to be an effective approach for adults with depressive symptoms. It provides support for the idea that a multidimensional intervention focused on promoting whole-person functioning can alleviate these symptoms. Lessons learned from this study can be used to guide evaluation strategies for a controlled trial, which is an important next step in research on this intervention.Clinical trial registrationhttps://ensaiosclinicos.gov.br/rg/RBR-776skr9, identifier RBR-776skr9.